PENGARUH PENGOLAHAN TANAH DAN PUPUK ORGANIK BOKASHI TERHADAP PERTUMBUHAN DAN HASIL TANAMAN KEDELAI (Glycine max L.) KULTIVAR WILIS - Suryaman Birnadi Birnadi (JURNAL ISTEK, 2014)
An experiment was conducted to study growth and yield of soybean with bokashi at various dosages and frequency soil tillage. Result showed there are interaction effect between the application of Bokashi and frequency soil tillage to dry plant weight soybean on optimum combination b2 p2 (bokashi 10 t ha-1 and twice soil tillage). Bokashi dosage level b2 (10 t ha-1) effect to the plant height and wilt of dry grain. Bokashi dosage level b3 (15 t ha-1) effect to effective nodule, leaf area, and yield of dry grain. Frequency level at once soil tillage (p1) effect to the plant height, effective nodule, and leaf area.